Dampak Implementasi Akuntansi Sosial dan Lingkungan terhadap Keberlanjutan Perusahaan: Studi pada Sektor Kehutanan dan Perkebunan - Gafrila Nibrasshadid Purwant; Ersi Sisdianto (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to identify the relationship between environmental accounting and environmental performance of plantation companies listed on the Indonesia Stock Exchange. It is hoped that this research will provide input for the plantation industry in the process of formulating disclosures. Sufficient place. The secondary data used in this study are annual reports and PROPER assessment results of the Ministry of Environment and Forestry for plantation companies listed on the Indonesia Stock Exchange. This study used purposive sampling method, and road analysis was used. To determine the effect of the intervention variables in the study, the sobel test was used. The research shows that environmental accounting has a positive impact on environmental performance; the better the implementation of environmental accounting, the better the environmental performance; then, corporate social responsibility has a positive impact on environmental performance; and, the higher the disclosure of corporate social responsibility, the higher the value of environmental performance, and corporate social responsibility as an intervention variable.